Inventory Management of Educational Facilities and Infrastructure at State Vocational High School 2 Pekanbaru - Fathur Rozak; Irawati Irawati; Hasgimianti Hasgimianti; Musa Thahir (Tarbawi, 2020)
This research aims to obtain information on the inventory management of educational facilities and infrastructures, as well as the supporting and inhibiting factors at State Vocational High School 2 Pekanbaru. This study used a descriptive qualitative approach by utilizing some data collection techniques such as a transcript, coding, and data interpretation. The results of this study showed that 1) the inventory management of the educational facilities and infrastructures had been good, it was seen by recording, classification, and coding based on the history purchase of goods. Moreover, reporting and removing the inventory had been based on the warrant by education authorities. 2) The supporting factors were the cooperation between the people at the school and adequate facilities and it has been well-formatted on the computer. Meanwhile, the obstructing factors were a large number of goods, low human resources, and relatively old age. The researcher hopes this study could be applied to be inventory guidelines for schools.